MENINGKATKAN KEMAHIRAN MOTORIK KASAR ANAK PRA SEKOLAH DI RA BAITUSSALAM CIMAHI MELALUI BERMAIN ANGKLUNG - siti yani aisyah; Fitriyani Solihat Solihat (IKIP Siliwangi, 2019)
Abstract Learning activities in kindergartens was implemented through play activities. In carrying out the principle of learning in kindergarten there is a lot of learning strategies that can be use, one of them with